Novel TOR1A mutation p.Arg288Gln in early-onset dystonia (DYT1). Issue 12 (13th May 2008) - Zirn, B; Grundmann, K; Huppke, P; Puthenparampil, J; Wolburg, H; Riess, O; Müller, U
Abstract : Background: The three-nucleotide deletion, GAG (within the gene TOR1A ), is the only proven cause of childhood-onset dystonia (DYT1). A potentially pathogenic role of additional sequence changes within TOR1A has not been conclusively shown. Methods: DNA sequencing of exon 5 of TOR1A in a patient with DYT1. Results: Detection of sequence change c.863G>A in exon 5 of TOR1A in the patient. The G>A transition results in an exchange of an arginine for glutamine (p.Arg288Gln) in subdomain α5 of TOR1A. Several findings point to a potentially pathogenic role of the sequence change in the patient: The base change is absent in 1000 control chromosomes; an Arg at position 288 of TOR1A has been conserved throughout vertebrate evolution, indicating an important role of Arg288 in TOR1A function; functional studies demonstrate enlarged perinuclear space in HEK293 cells overexpressing TOR1A with the p.Arg288Gln mutation. The same morphological changes are observed in cells overexpressing the common GAG TOR1A mutation but not in cells overexpressing wild-type TOR1A . Conclusions: The sequence change described here may be a novel pathogenic mutation of TOR1A in DYT1.